2011
DOI: 10.1021/je201008x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Iron(III) with 2-Hydroxybenzoic Acid in Aqueous Solutions

Abstract: The complex formation between the Fe 3+ ion and 2-hydroxybenzoic acid (salicylic acid, H 2 L) has been studied at 298.15 K in 1.05 mol 3 kg À1 NaClO 4 medium by both potentiometric titrations with glass electrodes and spectrophotometric measurements in the range of wavelengths between (410 and 600) nm. The concentrations of ligand (C L ) and metal ion (C M ) were varied between (0.105 Â 10 À3 and 21 Â 10 À3 ) mol 3 kg À1 , and the ligand-to-metal ratio was varied between (1 and 1000) (1 e C L / C M e 1000). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Spectrophotometric procedures have also been used to establish the stability constants of Fe(III) salicylates [6]. Alternatively, the stability constants can be determined using potentiometric titrations [7][8][9][10]. In the course of such experiments, different complex structures and compositions have been proposed, but, to our knowledge, none of them have been characterized by a crystal structure analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Spectrophotometric procedures have also been used to establish the stability constants of Fe(III) salicylates [6]. Alternatively, the stability constants can be determined using potentiometric titrations [7][8][9][10]. In the course of such experiments, different complex structures and compositions have been proposed, but, to our knowledge, none of them have been characterized by a crystal structure analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In order to confirm the speciation model and the formation constants gained via potentiometry by spectroscopic techniques as already established for other systems [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], spectrophotometric titrations on solutions containing Mn 2+ and Amp at t = 25 °C and I = 0.15 mol L −1 were performed under different concentration conditions. As an example, experimental spectra recorded on solutions containing Mn 2+ and Amp at C M = 0.05 mmol L −1 and C L = 0.05 mmol L −1 , were depicted in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, DHEA was found to reduce the levels of PGE 2 and other COX-2-derived eicosanoids without affecting COX-2 at gene expression level [21]. COX-2 represents a potential therapeutic target in many inflammation-associated disorders [35,36,37,38]. In addition, in the present work, we demonstrated that the apparent anti-inflammatory effects found in the murine RAW 264.7 macrophages could be reproduced in a cell line of human origin, as we found that MCP-1 and IL-6 production was decreased upon treatment with EPDA, at the concentration of 1 µM, in LPS-stimulated THP-1 macrophages.…”
Section: Discussionmentioning
confidence: 99%